2005
DOI: 10.1002/ijc.20964
|View full text |Cite
|
Sign up to set email alerts
|

Dietary and other risk factors in women having fibrocystic breast conditions with and without concurrent breast cancer: A nested case‐control study in Shanghai, China

Abstract: Risk of breast cancer is increased in women with proliferative benign breast conditions. Most of these conditions, however, do not progress to breast cancer. The purpose of our study was to identify factors possibly associated with this progression. Women with proliferative fibrocystic breast conditions alone (214), and women with proliferative fibrocystic breast conditions and concurrent breast cancer (130), were compared to each other, and each of these groups of women were also compared to 1,070 controls; a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 49 publications
2
42
0
Order By: Relevance
“…In addition, three publications shared the data from the Shanghai Breast Cancer Study, with almost the same cases (19,21,32). Two publications from a randomized trial of breast self-examination in Shanghai had to be considered as one study (28,30). However, two studies reported by Horn-Ross et al originated from different projects: the Bay Area Breast Cancer Study (case-control study) (20) and the California Teachers Study (cohort study) (36).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, three publications shared the data from the Shanghai Breast Cancer Study, with almost the same cases (19,21,32). Two publications from a randomized trial of breast self-examination in Shanghai had to be considered as one study (28,30). However, two studies reported by Horn-Ross et al originated from different projects: the Bay Area Breast Cancer Study (case-control study) (20) and the California Teachers Study (cohort study) (36).…”
Section: Resultsmentioning
confidence: 99%
“…Eligible cases, defined as women who had a breast biopsy and were diagnosed with either a fibrocystic breast condition or breast cancer, were selected from studies of mammary epithelial cell proliferation and breast cancer conducted between September 1995 and July 2000 (Wu et al [53];Li et al [54];Shannon et al [55]). In these studies, 551 (89%) of the 622 eligible women with fibrocystic conditions and 376 (88%) of the 426 eligible women with breast cancer were interviewed.…”
Section: Study Population and Settingmentioning
confidence: 99%
“…Exposures and reproductive lifestyle factors that modulate steroid hormones are associated with both breast cancer and fibrocystic breast conditions (4).…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiologic studies of the relationship between intake of soy foods and breast cancer have yielded inconsistent results (7). One study found a significant inverse association between soy food intake and risk of proliferative fibrocystic breast conditions, but not of nonproliferative fibrocystic conditions, or of breast cancer with or without concomitant proliferative fibrocystic conditions in extratumoral tissue (4). For the most part, these studies have relied on estimating soy and isoflavone intake using food frequency questionnaires or other dietary report instruments.…”
Section: Introductionmentioning
confidence: 99%